Distribution of Candida albicans and Non-albicans Candida Species Causing Vaginitis in Iran: A Review - OmeFarveh Rostami; Hossein Zarrinfar (Patient Safety and Quality Improvement Journal)
Introduction:Due to the rising prevalence of non-albicans Candida (NAC) species in vulvovaginal candidiasis (VVC), the present study on the geographical distribution of C. albicans and NAC species in Iran is of considerable importance. Early identification of rare species can significantly improve prevention and treatment strategies, thereby contributing to meaningful advancements in this field. Materials and Methods: This review examined studies conducted in Iran between 2009 and 2024, published in both Persian and English languages in the Google Scholar database. These studies covered reports from various cities, including Zabol, Gorgan, Sari, Damavand, Ilam, Tehran, Jahrom, Ahvaz, Birjand, Mashhad, Kerman, Babol, Qazvin, Ardabil, Babolsar, Shiraz, Yasuj, Gonabad, Kashan, Fasa, Torbat-e Jam, and Neyshabur. Results: The NAC species reported in Iran included C. glabrata, C. krusei, C. tropicalis, C. parapsilosis, C. kefyr, C. africana, C. lusitaniae, C. guilliermondii, C. orthopsilosis, C. dubliniensis, C. sake, C. intermedia, and C. famata. The highest prevalence of VVC in Iran was attributed to C. albicans, with a prevalence rate of 66.1% (2,975 out of 4,500 VVC cases), which is relatively high on a global scale. The NAC species accounted for 24.9% of cases (1,121 out of 4,500 VVC cases), with C. glabrata being the most common NAC species and exhibiting a prevalence rate of 11.7% (530 out of 4,500 VVC cases). Conclusion: The distribution of NAC species across various cities and regions of Iran has revealed significant variations. The reported species not only differ between cities but also within different areas of the same locality, emphasizing the need for localized surveillance and region-specific treatment strategies.